(3cTa GdHjGf Yf UaGJ GdMjhGfs - (3eMeO Hf eMeO Hf Ydj GHf YWjI GdYhaqj, GdEScfOQj GdCUd, GdeRj Ke GdYGJcj, CHh GdaJM, TeS GdOjf,J (B906 (3g` s
(3ChdgG (B:s
(3GdEaQL s
(3Vef eLehY , JQJjHgG (B: (3GdJGSYs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B53 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B248s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B176 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs